Determination of perception level of primary school teachers on organizational identity - Ozan, Mukadder Boydak; Sener, Gonul (Elsevier Science Bv, 2013)
Today institutions tend to create a distinctive identity to indicate their differences from their competitors and to get themselves accepted by the society. Institutional identity has great importance in terms of motivation and increasing employees' efforts to achieve institutional goals by the trust and collaboration will. The purpose of this study is to determine the primary school teachers' opinions on the perception of the organizational identity, to analyse whether the teachers' opinions change according to the variety of gender, professional experience, educational level and field of study. The results of this quantitative study indicate that majority of the teachers have a positive perception for their organizations. (C) 2013 The Authors. Published by Elsevier Ltd. Selection
3rd World Conference on Learning, Teaching and Educational Leadership (WCLTA) -- OCT 25-28, 2012 -- Brussels, BELGIUM
Keywords: Teacher; organizational identity; organizational culture; organizational climate; organizational communication